PHENOMENOLOGICAL APPROACH IN INTERFAITH COMMUNICATION: A Solution to Allegation of Religious Blasphemy in Indonesia - Yuangga Kurnia Yahya (IAIN Ponorogo, 2018)
Abstract: This paper will research the phenomenological approach in interfaith communication. The strength globalization’s flow which is destroying every border between nations, regions, and cultures, unfortunately, is not strong enough to destroy one solid wall, the border of religion and faith’s differences. The phenomenological approach is a theoretical perspective based on the concept “back to the things themselves”. In Husserl’s phenomenology, he made an epoche and eidetic vision as the starting point of this perspective. Both of those concepts are a main and basic concept which is needed in interfaith communication to postponing judgment and looking with their own believer’s perspective. This approach is radically needed to smooth out the interfaith communication. This approach also allows the transcultural communication and identity transformation from one religion’s followers to another to reach a mutual agreement and decrease religious sentiments which are born from the subjectivity of one religion’s followers in judging other religions and their followers. In the end, al-Banna’s Role of Brotherhood can be interpreted as the foundation of Islamic phenomenology in building the solid society.الملخص: عنى هذا البحث الكلام عن المنهج الظواهري في الاتصال بين الأديان. قوة موج العولمة التي تهاجم الحدود بين البلدان والمناطق والثقافات لم تكن تقوى على هجوم جدار متين، وهو جدار اختلاف الأديان والإيمان. المنهج الظواهر هي إحدى وجهة النظر القائمة على أساس